BIOMECHANICAL ASPECTS OF INTRACRANIAL INJURIES CAUSED BY FALLS FROM THE HEIGHT OF “OWN HEIGHT” ONTO THE SURFACE - Huseynova, G.A. (World of Medicine and Biology, 2024)
The main purpose of the study was to analyze the biomechanical conditions of intracranial injuries caused by a fall from “own height”. The study was based on the analysis of forensic medical examination materials, examination data, and a preliminary investigation of 190 people falling to the surface from their “own height”. The victims were divided into 6 age groups (